The case of the glow-in-the-dark ghost - Preller, James (Preller, James. Jigsaw Jones mystery, 2004)
Jigsaw's school is haunted! Some kids saw a ghost dancing in the classroom. Jigsaw Jones is not afraid. He will catch this glowing ghost...even if he has to stay after school to do it!